2016
DOI: 10.1002/cam4.720
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic slice cultures of human gastric and esophagogastric junction cancer

Abstract: Gastric and esophagogastric junction cancers are heterogeneous and aggressive tumors with an unpredictable response to cytotoxic treatment. New methods allowing for the analysis of drug resistance are needed. Here, we describe a novel technique by which human tumor specimens can be cultured ex vivo, preserving parts of the natural cancer microenvironment. Using a tissue chopper, fresh surgical tissue samples were cut in 400 μm slices and cultivated in 6‐well plates for up to 6 days. The slices were processed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…NSCLC slices cultured on rotating incubation units, to ensure continuous oxygenation, were fragile and showed dynamic culture‐induced changes, most prominently altered proliferation and mTORC1 hyperactivation. Although previous reports showed sustained viability of clinical tumour slices for 4–14 days , these studies derived conclusions from the selective analysis of cultured slices, whereas we systematically compared neighbouring cultured and uncultured slices. Furthermore, our study is the first to deeply analyse intratumour oncogenic signalling, and shows that signalling and proliferation alterations take place prior to overt changes in viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCLC slices cultured on rotating incubation units, to ensure continuous oxygenation, were fragile and showed dynamic culture‐induced changes, most prominently altered proliferation and mTORC1 hyperactivation. Although previous reports showed sustained viability of clinical tumour slices for 4–14 days , these studies derived conclusions from the selective analysis of cultured slices, whereas we systematically compared neighbouring cultured and uncultured slices. Furthermore, our study is the first to deeply analyse intratumour oncogenic signalling, and shows that signalling and proliferation alterations take place prior to overt changes in viability.…”
Section: Discussionmentioning
confidence: 99%
“…Within the IMI‐PREDECT project (http://www.predect.eu), we developed a workflow for short‐term culture of tumour slices, and showed that organotypic supports and atmospheric oxygen are strict requirements for tissue viability . A number of other studies have shown that responses to cytotoxic agents or selected targeted compounds can be modelled in clinical tumour‐derived slices . However, the question remains of how the in situ spatial signalling heterogeneity affects the pharmacodynamics of signalling inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…2B). Finally, we observed VacA-dependent inhibition of mTORC1 signaling activity within an ex vivo gastric tissue slice model derived from the stomachs of C57BL/6J mice (Koerfer et al, 2016) (Fig. 2C).…”
Section: Resultsmentioning
confidence: 79%
“…As an alternative, ex vivo culturing of tumor slices represent a solid model system for drug sensitivity testing due to its relatively short generation time and reflection of the tumor microenvironment . For example, several studies have shown that breast tumor tissue slices can be used to assess chemotherapy response in the context of personalized medicine .…”
Section: Introductionmentioning
confidence: 99%